Christians Labeled as Kafir in Indonesia: Is it an Apodictic Stance of Muslim? - Abin, Blasius (Budapest International Research and Critics University, 2021)
This paper addresses the issue of whether the kafir label for Christians in Indonesia is an apodictic stance of Muslims. The kafir label for Christians is grounded on the Al-Maidah 5:73 and Al-Maidah 5:17. These two texts indicate that those who believe in “Allah is the third of the three,” (Al-Maidah 5:73) and “God is the Messiah, son of Maryam” (Al-Maidah 5:17) are considered as “disbelievers” (kafir). This paper investigates the scholarly works of Muslims to answer the question. The following are the conclusions. First, Muslim scholars mostly disagree to affirm that these two texts attest that Christians are kafir. Christians believe in one God (monotheism) and this tenet is not the same as believing in the three Gods (polytheism) as Muslims have ascribed to Christians. Besides, Christians believe that Jesus is God, and this belief has been reiterated by the few texts of the Qur’an. Thus, if the kafir label for Christians is due to their tenet of the Trinity, it contradicts the biblical theology. Second, Muslim expositors ignore the literal context in the exposition of the two texts. The literal context of two texts has affirmed that Jesus is God and the Ruler of this universe. If the ground of the kafir label is due to the Christian tenet that Jesus is God, it devastates the biblical theology and the Qur’an per se. Thus, the kafir label for Christians at this point emerged from the superficial hermeneutic of Al-Maidah 5:73 and Al-Maidah 5:17. In the Indonesian context, the disaffirmation for the kafir label is incorporated by the prohibition of Nahdlatul Ulama, the largest Islam organization, to stigmatize kafir for Christians.